PERAN KOMUNIKASI DALAM EFEKTIVITAS OPERASIONAL KEPOLISIAN - Alyaa Mahira; Ajeng Cahya Lestari, Dimas Elfian Nazar, Fauzi Triastianto, Tugimin Supriyadi (Jurnal Komunikasi, 2024)
This study aims to determine the effect of communication, group cooperation, leadership and decision making on the performance of police officers (case study in the Secretariat Unit of the North Sumatra Regional Police). The results of the study that the Communication variable has no significant effect on the Police Member Performance variable. That the Group Cooperation variable has a significant effect on the Police Member Performance variable. That the Leadership variable has no significant effect on the Police Member Performance variable. That the Decision Making variable has a significant effect on the Police Member Performance variable That Communication, Group Cooperation, Leadership, and Decision Making have a significant effect together (simultaneously) on the Police Member Performance variable. Seeing the results of this study which shows that Group Cooperation and Decision Making are good. So the North Sumatra Regional Police Secretariat Unit is expected to continue to maintain Group Cooperation and Decision Making in order to improve the Performance of Police Members which of course will also have a positive impact on the North Sumatra Regional Police Secretariat Unit